Novel ultrafiltration membranes from low-fouling copolymers for RO pretreatment applications. Issue 48 (20th October 2016) - Krüger, Ralf; Vial, Denis; Arifin, Davis; Weber, Martin; Heijnen, Martin
Abstract: For a consistent and reliable ultrafiltration (UF) membrane operation, the membrane flux level has always been determined conservatively so that fouling rate is controllable, and therefore, chemical cleaning requirements are minimized. A better solution is to prevent the fouling to happen in the first place by modifying the surface properties of the membrane materials. This paper presents novel approaches to improve the fouling-propensity performance of existing UF membranes based on polyethersulfone. More hydrophilic membranes and anti-adhesive membranes were developed by using various novel copolymers as base membrane materials or as an additive in the spinning process. Incorporating these copolymers, improved Multibore® fibers were produced and validated in multiple pilot trials for various applications, namely surface and wastewater purification and seawater reverse osmosis pretreatment for desalination. The paper demonstrates that, for each application, a reduced fouling propensity performance was achieved, allowing the fibers to be operated at a substantially higher flux of up to 30%. This study underscores the importance of chemistry in obtaining low-fouling and high-performance UF membranes by modifying their surface properties.